REVIEW ON HISTORY OF TEACHING FOREIGN LANGUAGE METHODOLOGY AT UNIVERSITIES (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article aims to provide students with functional language skills that support their professional development, allowing them to communicate effectively in international settings, engage with academic research, and participate in globalized work environments. The integration of language learning with subject-specific content helps foster motivation, as students see immediate relevance to their personal and professional goals.